Analysis of Burial History for Mesopotamian basin, southern Iraq - Handhal, Amna; Al-Shahwan, Muwafaq; Al-Yaseri, Abdulla (Iraqi Journal of Science, 2023)
In this study, different oil fields in Mesopotamian basin, southern Iraq (Siba, Zubair, Nahr - Umr, Majnoon, Halfaya, Kumait, and Amara) were selected for studying burial history. PetroMod software 1D was used for basin constructing and to evaluate burial history of the basin. Results showed that in the upper Jurassic to the Recent, Mesopotamian Basin exhibited a complex subsidence history over a period of about 152 Ma.There are different periods of subsidence: high, moderate, and slow. High subsidence occurred at upper Jurassic- mid Cretaceous and at Miocene due to Tectonic subsidence. Slow subsidence occurred at upper Cretaceous and moderate subsidence at Paleogene. In the upper Jurassic, rapid subsidence is driven under the effect of sediment load during Suaily deposited. The average total subsidence values of the basement during the deposition of Suaily Formation is reached about 200 m. The highest subsidence rates during this time are observed northeast of the study area. Rapid subsidence in the lower Cretaceous, during deposition of Yammama, Ratawi, and Zubair formations. The average tectonic subsidence value of the basements during the deposition of Yammam Formation is reached to 300 m. The highest subsidence rates are observed trend to south west of the study area.